A Multi-Trait Comparison of an Urban Plant Species Pool Reveals the Importance of Intraspecific Trait Variation and Its Influence on Distinct Functional Responses to Soil Quality - Borowy, Dorothy; Swan, Christopher M. (Frontiers in Ecology and Evolution, 2020)
Mounting evidence indicates that the inclusion of intraspecific trait variability (ITV) can strengthen the signal of trait-environment relationships, as well as provide insights into the eco-evolutionary strategies that allow species to establish and persist in different environments. Such information is particularly valuable in urban systems where unique environmental conditions impose strong filtering effects on resident species and where, despite such pressures, high proportions of non-native species persist. In an effort to elucidate functional trait patterns of an urban species pool, we experimentally assessed the effect of soil on trait patterns of 56 plant species collected as seeds from vacant land in Baltimore City, MD, United States. We assessed the relative importance of explained trait variation at different ecological levels by decomposing the variance of six measured traits into three levels: within-species (ITV), between-species (BTV), and across functional groups (FGTV). We then compared functional responses – classified by differences in mean and variance patterns of trait values – across species, traits, and functional groups. Mean trait values varied in response to species and soil (urban vs. potting soil) for all traits, except root ash-free dry mass (AFDM) for soil. Variance decomposition of the species factor into each level showed that variance patterns for species were trait-specific, however, ITV explained a substantial proportion of the total variance for the majority of study traits. When accounting for mean and variance trait patterns between soil types, we found that species with specialized strategies (i.e., C4 photosynthesis and legumes) exhibited functional responses consistent with preadaptation, as defined by no change in the mean or the variance of trait values between soil types, for all traits. Native species showed higher proportions of trait divergence, as defined by shifts in mean trait values between soil types, but not change in variance, relative to introduced species, which showed higher proportions of preadaptation for all traits except specific leaf area (SLA). Species exhibiting trait constriction, or no shift in the mean but a significant change in the variance between soil types, consistently showed decreased variance in urban soil, which supports the idea that urban soils impose strong filtering effects that constrain species trait values. Overall, our study indicates that accounting for ITV, and how it relates to general functional responses associated with changes in the mean and variance of trait values, can provide a clearer understanding of the eco-evolutionary dynamics of plant species in urban environments.